Konsep Kepemilikan Tanah Ulayat Masyarakat Adat Minangkabau - Citrawan, Fitrah Akbar (Jurnal Hukum & Pembangunan, 2020)
Land is a very important factor in the life of the people of Indonesia, especially in the environment of the West Sumatra customary law community, where most of its population depend their lives and livelihoods from the land. In West Sumatra, in reality there are still acknowledged lands in the customary law community whose management, use and use are based on the provisions of local customary law and are recognized by the residents of the customary law community as their communal land. Ulayat Land Minangkanbau in the concept of ownership includes in the narrow sense that it is in the form of assets classified as high heirlooms that have force in and out both can be used by members of the community or outside the community by giving “adat diisi limbago dituang” with the main principle of customary land not can be sold and pawned except with the agreement of all members of indigenous peoples in certain circumstances such as “Mait terbujur di tengah rumah”, “Rumah gadang ketirisan”, “Gadih gadang indak balaki”, or “Membangkik batang terandam”.